Screening and evaluation of lactic acid bacteria with probiotic potential from local Holstein raw milk - Zhang, Wenqing; Lai, Shiji; Zhou, Ziyao; Yang, Jinpeng; Liu, Haifeng; Zhong, Zhijun; Fu, Hualin; Ren, Zhihua; Shen, Liuhong; Cao, Suizhong; Deng, Lei; Peng, Guangneng (Frontiers in Microbiology, 2022)
There are massive bacteria in the raw milk, especially the lactic acid bacteria (LABs), which have been considered probiotics in humans and animals for a long time. Novel probiotics are still urgently-needed because of the rapid development of the probiotic industry. To obtain new LABs with high probiotic potential, we obtained 26 LAB isolates, namely L1~L26, from local Holstein raw milk collected from a farm whose milk had never been used for LAB isolation. We identified them at the species level by biochemical and 16S rDNA sequencing methods. Their antagonistic activity against four target pathogens (Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa PAO1, and Salmonella enterica H9812), co-aggregative ability with these target pathogens, survivability in the simulated gastrointestinal tract conditions and phenol, auto-aggregation and hydrophobicity, hemolytic activity, and antibiotic susceptibility, were evaluated in vitro. Five Lactiplantibacillus plantarum isolates (L5, L14, L17, L19, and L20) showed more promising probiotic potential than others. Specifically, these five isolates conglutinated with and inhibited all the target pathogens, endured the simulated gastric juice (92.55~99.69%), intestinal juice (76.18~83.39%), and 0.4% phenol (76.95~88.91%); possessed considerable auto-aggregation (83.91~90.33% at 24 h) and hydrophobicity (79.32~92.70%); were non-hemolytic, sensitive to kinds of common antimicrobials. Our findings demonstrated that these five isolates could be preliminarily determined as probiotic candidates. This study highlighted the potential again of raw milk for probiotic isolating and screening and provided the probiotic industry with five new LAB candidates with promising probiotic potential.